Land management, crop production, and household income in the highlands of Tigray, northern Ethiopia: An econometric analysis - Pender, J.L.; Gebremedhin, Berhanu (International Food Policy Research Institute, 2006)
This paper is divided in sections. The first section deals with empirical model, methods, and hypotheses and looks into methods, data Sources, econometric approach, and predicted Impacts of selected variables. The second one discusses agriculture and land management in the highlands of Tigray with particular emphasis on biophysical and socioeconomic conditions, results of econometric analysis, and direct and indirect effects on production and income. The third section, key findings and implications examines population pressure, access to roads and markets, income strategies, irrigation, agricultural extension and credit, and endowments of physical, human, and social capital. The study is based on econometric analysis of household and plot-level surveys conducted in 100 villages in 50 tabias (the lowest administrative unit in Tigray, usually comprising four or five villages) in the highlands of Tigray during 1999-2000. It builds on a prior study based on tabia- and village-level surveys in the same communities in 1998-99 (Pender et al. 2001), which were used in the empirical work Reported in Chapter 4. This broad sample and the information collected at different levels enable investigation of the impacts of community-level factors such as population density, investments in irrigation and roads, as well as household and plot-level factors such as household wealth, education., education, land tenure, and other factors on land management and the implications for agricultural productivity and land degradation.